THE CORRELATION OF FAMILY KNOWLEDGE AND BEHAVIOR IN CONTROLLING HYPERTENSION IN PATIENTS AT OUTPATIENT DEPARTMENT - Elisabeth Nainggolan; Gracelia Sopacua; Regy Lodiay; Martina Pakpahan; Dora Irene Purimahua (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2021)
There has been a significant and continuous increase in the number of people suffering from hypertension worldwide, particularly in Indonesia. Many families with hypertensive members do not recognize hypertension or control their hypertension. This study aims to determine the correlation of family knowledge and behavior in controlling hypertension in patients at the outpatient department of a private hospital in Jakarta. The method was a quantitative methodology with a cross-sectional design approach. The population was the patients’ families in outpatient department. The sample was 94 respondents who were selected using the purposive sampling technique. The instrument was a previous study's questionnaire. The univariate analysis showed that 64.9% of respondents have good knowledge, and 53.3% have good behavior. The bivariate analysis, which used the Pearson Chi-Square test showed a p-value of 0.001 (CI 95%). There was a correlation between family knowledge and behavior in controlling hypertension in patients at the outpatient department. Hospitals and nurses can further optimize family education, socialization, and collaboration in controlling hypertension.